Gaming Disorder and Well-Being Among Emirati College Women - Verlinden, Marina; Thomas, Justin; Almansoori, Mahra Hasan Abdulla Ahamed; Wanigaratne, Shamil (Frontiers in Psychiatry, 2021)
Background: The present study examined IGD and depressive symptom levels among a predominantly female sample of college students from the United Arab Emirates (UAE). Methods: IGD was assessed among two successive cohorts of students at the beginning of the academic year in 2016 and 2019, respectively. All participants (n = 412) completed the Internet Gaming Disorder Scale – Short-Form (IGDS9-SF) and the WHO-5 Wellbeing Index (WHO-5), a tool widely used for the screening and assessment of depressive symptomatology. Results: Mean IGDS9-SF scores (15.85, SD = 6.40) were fairly similar to those observed in other nations. The prevalence of IGD was 1.45%, based on the stringent cut-off score (>= 40). Prevalence of IGD rose to 18.20% when using the less stringent cut-off (>= 21). There was an increase in the rate of IGD between 2016 and 2019, although not statistically significant. Higher IGDS9-SF scores were associated with greater depressive symptomatology; those scoring above the less stringent IGD cut-off had a greater likelihood of screening positive for depression OR= 2.28, 95% CI [1.176 – 4.428]. Conclusions: This study provides insights about IGD among a predominantly female Arab population, finding a correlation with mood disorder symptomatology and suggesting an increase in problematic gaming over time. The results are discussed with reference to the mood repair hypothesis and the possibility of IGD being a dual disorder. The association with depressive symptoms is also discussed in light of the neurobiology of addictive behaviors and sexual dimorphism.